Situation Report: Romania, 19 January 1973 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Ceausescu's Visit to Pakistan and Iran Twenty-Fifth Anniversary of the Republic Marked Chairman of National Union of Agricultural Integration of Higher Education Institutions with Production and Scientific Research Units Changes in the TV Program President of Comecon Investment Bank in Bucharest New Penal Code and Other Important Bills Expected Law on National Defense (II)